The Context for Opportunity in the United States for Young International Scholars - Denecke, Daniel D. (La Cuestión Universitaria, 2016)
Across Europe and the United States (U.S.), educators and policymakers are in agreement that a strong national system of graduate education is essential to a country is ability to innovate, to compete in the global economy, and to contribute to solving some of the most pressing challenges in areas ranging from energy, the environment, world health, and security. The strength of the U.S. graduate enterprise depends upon its critical infrastructure and leadership, on quality curricula and facilities, on partnerships with government and industry, and on a strong pool of domestic and international talent. Over the past three decades, international students have come to play an increasingly important role in this enterprise. Indeed, as global competition accelerates for the best students in every field, many universities in the United States are striving harder to ensure the continued attraction of study opportunities for young international scholars. They are doing this through increased sensitivity to the needs of international scholars and the challenges they face, through innovative "best practiceî initiatives to improve the quality of the graduate experience, and through collaborative agreements with institutions from other countries.